The Development and Optimization of Hot-Melt Extruded Amorphous Solid Dispersions Containing Rivaroxaban in Combination with Polymers - Jong-Hwa Lee; Hyeong Sik Jeong; Jong-Woo Jeong; Tae-Sung Koo; Do-Kyun Kim; Young Ho Cho; Gye Won Lee (MDPI AG, 2021)
Rivaroxaban (RXB), a novel oral anticoagulant that directly inhibits factor Xa, is a poorly soluble drug belonging to Biopharmaceutics Classification System (BCS) class II. In this study, a hot-melt extruded amorphous solid dispersion (HME-ASD) containing RXB is prepared by changing the drug:polymer ratio (Polyvinylpyrrolidione-vinyl acetate 64, 1:1-1:4) and barrel temperature (200-240 °C), fixed at 20% of Cremophor® RH 40 and 15 rpm of the screw speed, using the hot-melt extruding technique. This study evaluates the solubility, dissolution behavior, and bioavailability for application to oral drug delivery and optimizes the formulation of rivaroxaban amorphous solid dispersion (RXB-ASD). Based on a central composite design, optimized RXB-ASD (PVP VA 64 ratio 1:4.1, barrel temperature 216.1 °C, Cremophor® RH 40 20%, screw speed 15 rpm) showed satisfactory results for dependent variables. An in vitro drug dissolution study exhibited relatively high dissolution in four media and achieved around an 80% cumulative drug release in 120 min. Optimized RXB-ASD was stable under the accelerated condition for three months without a change in crystallinity and the dissolution rate. A pharmacokinetic study of RXB-ASD in rats showed that the absorption was markedly increased in terms of rate and amount, i.e., the systemic exposure values, compared to raw RXB powder. These results showed the application of quality by design (QbD) in the formulation development of hot-melt extruded RXB-ASD, which can be used as an oral drug delivery system by increasing the dissolution rate and bioavailability.